Crypto Fundamental Analysis: Comparison of Cryptos with the Largest Market Capitalizations - Kareena Hilwa; Sri Astuty; Diah Retno Dwi Hastuti; Muhammad Syafri; Regina Regina (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Cryptocurrency has become a rapidly developing digital asset class that attracts widespread investor interest due to its decentralized, anonymous, and highly volatile nature. Such volatility creates uncertainty in market movements, making it important to understand the factors that drive fluctuations in returns. This research aims to examine how fundamental indicators namely price, trading volume, and market capitalization affect return volatility, as well as to determine which cryptocurrency demonstrates the highest market efficiency based on risk assessment. The study uses panel data covering the five largest cryptocurrencies by market capitalization (Bitcoin, Ethereum, Tether, USD Coin, and Binance Coin) over the period 2019–2023. The analytical methods applied include panel data regression to identify the determinants of volatility and Value at Risk (VaR) to measure asset risk and efficiency. The findings show that price and trading volume positively and significantly increase return volatility, whereas market capitalization exerts a negative and significant effect, indicating its stabilizing role. Based on VaR analysis, Binance Coin (BNB) emerges as the asset with the highest market efficiency. The study concludes that fundamental indicators play a crucial role in shaping volatility and that BNB offers relatively better risk performance compared to its peers.